Image-sharing in Twitter-based professional conversations - Wilson, Anna N. (Proceedings of the International Conference on Networked Learning, 2016)
This paper reports on ongoing research into the image-sharing practices of two informal professional networks, one dedicated to midwives and the other dedicated to teachers, on Twitter. Each network is brought together through regular, loosely synchronous Twitter conversations, created through the use of an identifying hashtag. In both cases, the conversations have been initiated by practitioners with the explicit intention of creating a space for sharing ideas, practice, experience and opinions. Community members are relied on to provide facilitation, to promote the conversations and, in one case, to suggest conversations themes. These kinds of informal professional conversation may thus serve as somewhat hidden, but potentially influential, sites of professional learning. As with most social media and mobile communications, Twitter has become increasingly saturated with images. Indeed this may be a particularly strong trend on Twitter because images can be used to convey a great deal more than might easily be said in the 140 characters users are limited to in each tweet. Professional conversations are no exception to this, with images accompanying tweets with increasing frequency. Images, then, may provide a rich alternative to research focusing on the text of tweets. This paper describes research using such images as foci for the study of the flow of information, opinion and affect amongst the two professional groups described above. Starting with a period of extended observation of both conversations, the research proceeded to in-depth interviews with a small number of practitioners who were also active participants, in which images previously published during the Twitter conversations were used as prompts. Methods developed to visualise and make sense of the relations between images and users during the conversations, and ultimately to identify candidate interviewees and prompt images are described. The research makes use of philosopher Gilles Deleuze’s concepts of lines of articulation, lines of flight and knots to draw out some of the factors affecting flows through the conversation-spaces. It appears that there are at least three broad factors - the technical affordances for communication provided by Twitter, individuals’ notions of online professionalism, and individuals’ sense of the purpose of the conversation-space - that create lines of articulation and flight, constraints and uncertainties that accelerate, amplify or impede these flows. These lines twist and knot, resulting in a socio-technical disciplining that conditions the conversations and both reveals and hides aspects of professional life.